The Influence of Temple Monopoly (TEMON) Game on Historical Thinking Skills and Learning Independence in History Learning at SMA Negeri 4 Bekasi - Alfarez, Sidqi; M, Fakhruddin; Kurniawati (Mimbar Ilmu, 2025)
A common problem in Indonesia, especially in history learning, is the one-way (teacher-centered) lecture method, which results in non-interactive classes, lack of student independence, and limited improvement in student skills. Efforts to achieve learning objectives in the 21st century pose a challenge for schools and teachers to prepare effective classroom practices. The concept of using games in learning, known as Game Based Learning (GBL), is applied through the Temple Monopoly (TEMON) game. The goal is to stimulate students’ historical thinking skills and learning independence. The research method used was a Pre-Experiment Design with a quantitative comparative approach between an experimental class and a control class in 10th grade Senior High School (SMA). The research findings show that the average historical thinking skills and learning independence in the experimental class differed significantly from the control class. In conclusion, the T-test results indicated a value of 4.750 > 1.990, showing that TEMON has an impact on historical thinking skills, and the independent learning outcomes showed a T-test result of 1.970 > 1.664 at SMAN 4 Bekasi. Similarly, TEMON also positively impacts learning independence.